A Sustainable model for community-based tourism in the Muaro Jambi Temple Area, Jambi Province - Zulfanetti, Zulfanetti; Heriberta, Heriberta; Umiyati, Etik; Minati, Jurnia (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
This study investigates community participation concerning the potential and benefits of the Muaro Jambi Temple tourism area, identifying key success factors in community-based tourism (CBT). Employing Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis on primary data, this research combines descriptive and quantitative approaches. The findings reveal that variables related to interest, opportunity, and innovation significantly and directly impact economic conditions, while environmental factors notably influence social conditions. In contrast, cultural and political variables do not significantly affect social conditions. Both economic and social factors significantly influence CBT participation. Indirect effects analysis shows that interest, opportunity, innovation, and environmental factors significantly influence CBT participation, whereas cultural and political variables do not exhibit significant indirect effects. Moreover, over 95% of the communities in the villages surrounding Muaro Jambi Temple perceive the basic principles of CBT positively, with 85% recognizing the potential and benefits of supporting the CBT model. These results underscore the importance of fostering interest, opportunity, and innovation to enhance economic conditions and community participation in CBT initiatives.